Effect of Sand Particle Size on Sand–Water Flow in a Francis‐99 Distributor - Ziyao Zhou; Pinyu Xiang; Kang Xu; Jitao Liu; Yuanyuan Gang; Haiqi Wang; Jiayang Pang; Xiaobing Liu (Energy Science & Engineering)
ABSTRACT To examine the sand–water flow characteristics in the distributor of the Francis‐99 hydraulic turbine, numerical simulations were conducted using the Mixture multiphase flow model, focusing on the impact of varying sand particle sizes. The findings indicate that near‐wall velocities of sand and water in the fixed and guide vanes of the Francis‐99 hydraulic turbine range from 1.5 to 3.4 m/s and from 2.1 to 11.2 m/s, respectively, with the highest values observed at the tail section. The trajectories of smaller sand particles closely followed the water flow, whereas for particle sizes of around 0.3 mm, acceleration and deceleration processes showed a noticeable lag due to inertia, leading to significant velocity fluctuations compared to smaller particles. The sediment concentration on the front side of the stay and guide vanes initially increased and then decreased along the flow direction, whereas on the back side, a gradual reduction was observed, with the peak sediment concentration occurring at the head. As the sand particle size increased, the uniformity of the sediment concentration distribution on the guide vane surface decreased. When the average sediment concentration (volume fraction) in the flow field was 0.00095, the maximum concentration on the front side of the guide vane reached 0.0025, and the region of high concentration expanded, whereas the back side showed an opposite trend. The results further demonstrate that the arrangement of fixed and guide vanes influences the sediment concentration distribution in the sand–water flow within the hydraulic guide mechanism of the Francis‐99 hydraulic turbine, leading to inconsistencies in sediment distribution patterns on adjacent guide vane surfaces.